Protein C deficiency presenting as an acute infero-posterior ST elevation myocardial infarction in a young man; A case report and focused literature review. Issue 192 (August 2020) - Al Yaarubi, Razan; Al Rawahi, Bader; Al Lawati, Hatim
Highlights: Hereditary thrombophilias are an important diagnostic consideration acute myocardial infarction with normal coronary arteries An acute myocardial infarction can be the first presenting event in hereditary thrombophilias e.g. protein C deficiency Direct oral anticoagulants can substitute vitamin K antagonists for the management and prevention of arterial thromboembolic events.